Epidemiological profile of the elderly affected by dengue in the State of Pará in the historical series 2013-2017, Brazil (Research, Society and Development, 2020)
Introduction: The elderly population is part of a group more susceptible to contracting dengue and being more vulnerable to developing the severe form of the disease, due to the constant presence of diseases. In addition, half of the dengue death cases affect the population over 60 years of age. Objective: To trace the clinical and epidemiological profile of the elderly patient affected by dengue in the State of Pará, in the historical series from 2013 to 2017. Methodology: Quantitative, retrospective study, descriptive-exploratory aims to investigate in the scientific literature the behavior of dengue infections in the elderly population of Pará, in the 2013-2017 historical series. Results: A total of 2,215 dengue cases were found in the elderly from 2013 to 2017, with 1,393 (62.89%) of the public aged 60-69 years, followed by 615 (27.77%) cases from elderly people aged 70 -79 years old and 207 (9.35%) over 80 years old. Discussion: Brazil represents 390 million people infected by dengue annually. It is a disease that is directly related to behavioral circumstances. It is worth noting that some research variables showed significant values ​​of ignored / blank numbers, this allowed for reflection based on the literature, on the low degree of precision in the reported data. Conclusion: The infection causes a number of relevant cases, being relevant that the individuals who are part of the academic body and, especially, the health professionals have rigorous knowledge about the disease, considering its biological and social aspect, in order to provide a broader and humanized treatment.